Postępowanie w sprawie istotnego odstąpienia od zatwierdzonego projektu budowlanego lub innych warunków pozwolenia na budowę - Fronczak, Adam (Kwartalnik Prawa Publicznego, 2013)
The aim of this article is to discuss the administrative proceedings regarding significant deviations from an approved building project or other provisions concerning a building permit. These proceedings are settled in stages in the Act on Construction Law. Pursuant to Art. 50 Sec. 1 Item 4, a competent authority suspends, by means of a decision, the execution of construction works, which are performed in a manner significantly deviating from the terms and conditions stipulated in the building permit. Subsequently, prior to the lapse of 2 months from issuing the aforementioned decision, the authority, by means of the decision, imposes an obligation, simultaneously defining the date of completion, to make and submit a replacement building project, including amendments resulting from the hitherto performed construction works and, if necessary, to perform specific procedures or works in order to make the performed works consistent with the law (Art. 51 Sec. 1 Item 3). Depending on the actions taken by the Investor towards fulfilling this obligation, the proceedings end in two possible scenarios. After the expiration of the indicated term or upon the request of the Investor, the authority evaluates the execution of the obligation and renders a decision regarding the acceptance of the building permit and the resumption of construction works or a decision accepting the replacement building project, if the construction works are completed (Art. 51 Sec. 4). However, in case of a failure to execute the obligation on time, pursuant to Art. 51 Sec. 5, a decision prohibiting further construction works or ordering demolition of the object or its part, or bringing the object back to the previous state is rendered.